2002
DOI: 10.1093/jn/132.2.283
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Riboflavin and Plasma Total Homocysteine in the Framingham Offspring Cohort Is Influenced by Folate Status and the C677T Transition in the Methylenetetrahydrofolate Reductase Gene

Abstract: Methylenetetrahydrofolate reductase (MTHFR) catalyzes the synthesis of 5-methyltetrahydrofolate, the methyl donor for remethylation of homocysteine to methionine. The C677T MTHFR polymorphism is associated with mild hyperhomocysteinemia, but only in the presence of low folate status. Because MTHFR contains flavin adenine dinucleotide (FAD) as a prosthetic group, riboflavin status may also influence homocysteine metabolism. The objective of this study was to examine the association between riboflavin status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 21 publications
7
80
1
2
Order By: Relevance
“…On the other hand, this MTHFR genotype dependence could also be supportive of increased supplement use during follow-up as discussed above, as B vitamins are known to have a tHcy lowering effect especially in TT individuals (Jacques et al, 1996;Hustad et al, 2000;Jacques et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, this MTHFR genotype dependence could also be supportive of increased supplement use during follow-up as discussed above, as B vitamins are known to have a tHcy lowering effect especially in TT individuals (Jacques et al, 1996;Hustad et al, 2000;Jacques et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Whether an altered lifestyle and changes in lifestyle-related factors are associated with changes in tHcy have not been thoroughly investigated. The thermolabile variant of the methylenetetrahydrofolate reductase (MTHFR(C677T)) (Frosst et al, 1995), a regulating enzyme in tHcy metabolism, has been shown to modify the relation between several lifestyle factors and tHcy (Jacques et al, 1996;Hustad et al, 2000;Jacques et al, 2002;Husemoen et al, 2004). Thus the effect on tHcy of changes in lifestyle related factors may depend on MTHFR(C677T) genotype.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier animal study showed a significant association between vitamin B 2 and MTHFR that the enzyme activity and the relative amounts of 5-methyl THF were reduced in the liver of riboflavin-deficient rats (Bates & Fuller, 1986). Hustad et al (2000), McNulty et al (2002), and Jacques et al (2002) demonstrated that plasma vitamin B 2 was an independent determinant of plasma homocysteine, and this inverse dose-response relation was essentially confined to subjects with the C/T or T/T genotype of the MTHFR C677T polymorphism where the requirement of FAD for maximal catalytic activity might be increased (Hustad et al, 2000;Ueland et al, 2001). Several investigators have suggested that vitamin B 6 deficiency may lead to hyperhomocysteinemia, which is an established risk factor for adverse pregnancy outcome (van den Berg et al, 1994;Leeda et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have showed that B-vitamin status is a major determinant of tHcy in the general population (Jacques et al, 1996b(Jacques et al, , 2002Hustad et al, 2000;Moat et al, 2003). Little attention has been given to the effect of overall dietary pattern regarding tHcy.…”
Section: Discussionmentioning
confidence: 99%
“…Persons homozygous for the mutant T-allele have higher tHcy concentrations than persons with CC and CT genotypes (Husemoen et al, 2003). Moreover, the MTHFR(C677T) polymorphism has been shown to modify the relation between B-vitamin intake and tHcy (Jacques et al, 1996a(Jacques et al, , 2002Hustad et al, 2000). Suboptimal vitamin status is associated with much higher tHcy concentrations in persons with the TT genotype than in persons with the CC or CT genotypes.…”
Section: Introductionmentioning
confidence: 99%